The shifts of marketing communication in times of economic downturns in Indonesia - Purwaningwulan, Melly Maulin; Wulandari, Tine Agustin; Anggaswari, Niluh Ayu; Hong, Vu Anh (Jurnal Kajian Komunikasi, 2025)
Background: Economic downturns have compelled businesses in Indonesia to rethink marketing communication by adopting innovative, digital, and empathetic strategies in response to shifting consumer behavior, reduced budgets, and increased competition. Purpose: This research aims to explore the dual nature of marketing communication during economic downturns in Indonesia, examining both the key challenges businesses face and the innovative strategies they adopt to survive and thrive in turbulent times. Methods: The methodology used in this study is qualitative, employing descriptive analysis techniques that are consistent with the research objectives. Results: The global economic outlook for 2024-2025 remains uncertain, Indonesia has shown resilience through a strong export performance that supports its economy amid global trade challenges. In response to economic downturns, businesses in Indonesia have adopted innovative, digital, and emotionally driven marketing communication strategies that blend technology, creativity, and empathy to sustain consumer relationships and business resilience. The impact on consumer behavior is marked by declining consumer confidence, reduced purchasing power, and rising frugality. In times of crisis, government and corporate responses play a crucial role in shaping marketing communication. Conclusion: Amid global economic uncertainty and shifting consumer behavior, Indonesia’s resilience has been driven by adaptive marketing communication strategies that integrate digital innovation, emotional connection, and transparent messaging to sustain business continuity and public trust. Implications: This study offers practical insights for businesses to adopt adaptive, technology-driven, and empathetic marketing strategies during economic downturns, while also contributing theoretically to the understanding of crisis communication and consumer behavior in emerging markets in Indonesia.